Sentencing Disparities Against Corporations in Forest Destruction Crimes: An Analysis of Court Decisions - Fahrial Ansar; Hariman Satria; Faisal Abdaud (Greenation International Journal of Law and Social Sciences, 2026)
This study examines sentencing disparities against corporations in forest destruction crimes through an analysis of three Indonesian court decisions involving PT. Bososi Pratama, PT. Natural Persada Mandiri, and PT. Pertambangan Nikel Nusantara in the Lalindu protected forest area, North Konawe. The study uses normative legal research with a case approach and a conceptual approach. The case approach is used to examine the ratio decidendi, indictments, prosecutorial demands, criminal sanctions, and evidence status in each decision, while the conceptual approach is used to interpret the findings through doctrines of corporate criminal liability and sentencing disparity. The findings show that disparity does not only appear in the amount of criminal fines imposed by judges. It also emerges earlier in the criminal process through different forms of indictment, unequal prosecutorial demands, inconsistent criminal judgments, and different treatment of evidence originating from comparable sources. The theoretical contribution of this study lies in showing that sentencing disparity in corporate environmental crimes must be understood as a procedural and substantive problem, not merely as a difference in final punishment. The study is urgent because inconsistent sentencing in forest destruction cases can weaken legal certainty, reduce deterrence, and undermine the function of corporate punishment in restoring environmental harm and preventing repeated violations.